Modeling and parametric study for a two-phase loop passive containment cooling system. (August 2022) - Zhang, Keyuan; Zhou, Shaofei; Wu, Xiaotian; Li, Yaru; Chi, Xiangyu; Nan, Zezhao; Wang, Naihua
Highlights: A mathematical model considering filling ratio and noncondensable gas is developed. An optimization method is proposed to minimize the heat transfer area. The loop performance associates with the optimal filling ratio. The loop performance reduces as the noncondensable gas increases. Abstract: In this study, an optimization method is developed for the structure of the two-phase loop passive containment cooling system. The total heat transfer area of the passive containment cooling system is minimized. At the same time, a new mathematical model is developed with the considerations of the filling ratio and the noncondensable gas inside the loop. On the basis of the mathematical model, the performances of the passive containment cooling system with different filling ratios and noncondensable gas contents are evaluated. Parametric studies are further performed for the key parameters including the operating pressure in the containment, the filling ratio and the noncondensable gas content. The results indicate that the loop heat transfer rate is significantly influenced by these parameters. The effect of the filling ratio on the loop performance is highly related to the optimal filling ratio. The loop heat transfer rate can increase as the filling ratio increases, until the filling ratio reaches the optimal. In addition, the loop heat transfer rate drops by 34% as the noncondensable gas content increases from 0 to 10 kPa, while the corresponding optimal filling ratio increases. As the filling ratio is fixed at 0.56, the difference between the filling ratio and the optimal filling ratio can aggravate the inhibition of noncondensable gas on the loop performance. The reduction of the loop heat transfer rate increases to 37.5% as the noncondensable gas content reaches 10 kPa.